TEKNIK OPTIMASI ANIMASI ADOBE FLASH - Sany, Ezrifal (FORTECH (Journal of Information Technology), 2017)
Adobe Flash is one of the software to create an animation. Animation involves objects with complex motions, therefore the resulting file has a very large size, which causes the animation display to be slower. It takes a method in making an animation to minimize the resulting file size, which is called optimization technique. Optimization techniques are done in making the animation to make the file size becomes smaller, but the resulting animation quality remains the same. The quality of the animation is determined by the amount of movement generated by an object. Animated optimization results will have the same animated qualities with animations that do not use optimizations if both have the same number of motions.